PERAN DAN FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU GURU DALAM PENDIDIKAN KESEHATAN REPRODUKSI REMAJA SEKOLAH MENENGAH PERTAMA DI KABUPATEN SUBANG TAHUN 2019 - Juariah Juariah; joko irianto irianto (Jurnal Kesehatan Reproduksi, 2020)
Abstract Background: Teachers have an important role in providing reproductive health education for adolescents. Objective: To analyze the relationship of characteristics, training, knowledge, attitude, identities and school supports with teacher behavior in providing adolescent reproductive health education. Method: This study was an analytical research with cross-sectional design. The number of sampel were 71 schools that was determined by systematic random sampling. The number of respondents were 421 teachers. The independent variables were characteristics, training, knowledge, attitudes, identities and school supports. The dependent variable was teachers behavior in providing reproductive health education. Data were collected through interviews. The data were analyzed using Chi Square Test and multiple logistic regression. Result: Factors related to teacher behavior in providing adolescent reproductive health education were gender (OR: 1.64; 95% CI: 1.105-2.437), employment status (OR: 1.55 ; 95% CI: 1.03-2.34 ), training participation (OR:1.78; 95% CI: 1.210-2.623), knowledge (p: 0.000), attitude (OR: 5,81 ; 95% CI: 4.412-7.650), facilities (OR: 1749.52 ; 95% CI: 457.670-6688.005) and implementation (OR: 2008.95; 95% CI: 512.397-7876.487). The most dominant factors related to the teachers’ behavior in providing reproductive health education were facilities (OR: 110.49; 95% CI: 22.21-549.52) and implementation (OR: 139.28; 95% CI: 28.56- 679.30). Conclusion: Adequate support of learning facilites and aspects of implementation had major contribution to the behavior of teachers in providing reproductive health education. Keywords: teacher behavior, education, adolescent reproductive health Abstrak Latar belakang: Guru memiliki peranan penting dalam memberikan pendidikan kesehatan reproduksi pada remaja. Tujuan: Menganalisis hubungan karakteristik, pelatihan, pengetahuan, sikap, identitas dan dukungan sekolah dengan perilaku guru dalam memberikan pendidikan keehatan reproduksi remaja. Metode: Jenis penelitian ini adalah analitik dengan desain potong lintang. Sampel ditetapkan dengan systematic random sampling berjumlah 71 sekolah. Responden berjumlah 421 orang guru. Variabel independen adalah karakteristik, pelatihan, pengetahuan, sikap, identitas dan dukungan sekolah. Variabel dependen adalah perilaku guru dalam memberikan pendidikan kesehatan reproduksi. Data dikumpulkan melalui wawancara. Data dianalisis dengan uji Chi-square dan regresi logistik ganda. Hasil: Faktor-faktor yang berhubungan dengan perilaku guru dalam memberikan pendidikan kesehatan reproduksi remaja adalah jenis kelamin (OR:1,64; 95% CI: 1,105-2,437), status kepegawaian (OR: 1,55 ; 95% CI: 1,03-2,34 ), keikutsertaan pelatihan (OR:1,78; 95% CI: 1,210-2,623), pengetahuan (p: 0,000), sikap (OR: 5,81 ; 95% CI: 4,412-7,650), sarana (OR: 1749,52 ; 95% CI: 457,670-6688,005) dan pelaksanaan (OR: 2008,95; 95% CI: 512,397-7876,487). Faktor yang paling dominan berhubungan dengan perilaku guru dalam memberikan pendidikan kesehatan reproduksi adalah sarana (OR: 110,49; 95% CI: 22,21-549,52) dan pelaksanaan (OR: 139,28; 95% CI: 28,56- 679,30). Kesimpulan: Dukungan sarana pembelajaran yang memadai dan aspek pelaksanaan memiliki kontribusi utama terhadap perilaku guru dalam memberikan pendidikan kesehatan reproduksi. Kata kunci: perilaku guru, pendidikan, kesehatan reproduksi remaja